Barneveld College courses announced - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Barneveld College in the Netherlands (International Training Centre on Animal Husbandry and Milling Technology) has announced its international courses for the academic year 1989-1990. The Poultry Husbandry and Pig Husbandry courses will take place...